Nano-composite hydrogel based on active oxygen removal as well as preparation method and application of nano-composite hydrogel

Melatonin-loaded mesoporous polydopamine nanoparticles are encapsulated using a three-dimensional network framework formed by cross-linking of oxidized chondroitin sulfate and carboxymethyl chitosan by using reactive oxygen scavenging nanocomposite hydrogels in osteoarthritis treatment , solves the problems of hydrogel in osteoarthritis treatment and drug release stability, and achieves better drug activity and therapeutic effects.

CN119214996AInactive Publication Date: 2024-12-31QINGDAO UNIV

Patent Information

Application Number
CN202411432313.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-14
Publication Date
2024-12-31
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The existing hydrogels lack versatility in the treatment of osteoarthritis, weak mechanical properties, unstable drug release, and difficult to effectively control the drug release rate, affecting the efficacy of the drug.

Method used

Design a nanocomposite hydrogel based on reactive oxygen scavenge to form a three-dimensional network skeleton by cross-linking of oxidized chondroitin sulfate and carboxymethyl chitosan to encapsulate melatonin-loaded melatonin to achieve drug lengthening Effective release and anti-inflammatory effects.

Benefits of technology

This nanocomposite hydrogel has self-healing ability, good biocompatibility and mechanical properties, which can effectively reduce inflammation and oxidative stress, improve the symptoms of osteoarthritis, and provide better drug activity and therapeutic effects.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119214996A_ABST
    Figure CN119214996A_ABST
Patent Text Reader

Abstract

The invention discloses nano-composite hydrogel based on active oxygen removal as well as a preparation method and application of the nano-composite hydrogel, and relates to the technical field of biomedicine. The nano composite hydrogel based on active oxygen removal comprises a three-dimensional network skeleton structure formed by cross-linking oxidized chondroitin sulfate and carboxymethyl chitosan, and melatonin-loaded mesoporous polydopamine nanoparticles are encapsulated in the three-dimensional network skeleton structure. According to the invention, a nano material is combined with a three-dimensional network skeleton structure of the hydrogel, a novel nano composite hydrogel is developed, and the nano composite hydrogel has self-healing ability, good biocompatibility, good mechanical properties and long-acting drug release ability; meanwhile, the melatonin is loaded into the nano-composite hydrogel to develop a medicine compound, the medicine activity and the treatment effect are better than those of the melatonin, inflammation and oxidative stress can be relieved more effectively, and symptoms can be improved more effectively.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of biomedical technology, and in particular to a nanocomposite hydrogel based on active oxygen scavenging, and a preparation method and application thereof. Background Art

[0002] Osteoarthritis (OA) is a slow, degenerative joint disease characterized by changes such as reduced joint space and cartilage degeneration; clinical symptoms of OA include joint pain, swelling, and abnormal appearance. As the disease progresses, patients with OA may experience reduced physical activity, fatigue, sleep disorders, and even depression and disability.

[0003] At present, the treatment of osteoarthritis is mainly for the purpose of relieving pain, using non-surgical treatment and surgical treatment. Non-surgical treatment is drug treatment, which is mainly aimed at patients with early osteoarthritis found in clinical practice. There are two specific routes of drug treatment: systemic administration and local administration. Because drug administration is convenient and relatively inexpensive, drug treatment is easy for patients to accept.

[0004] Hydrogel is a polymer material with a three-dimensional network skeleton structure that can swell in water and maintain its shape. Currently, hydrogels are used in many fields, especially in the biomedical field, such as wound healing, tissue engineering, cell proliferation, and drug delivery. Among them, the combination of hydrogel and drugs has many potential advantages and applications, especially in drug delivery systems, which can achieve controlled release of drugs, improve drug stability, and reduce drug side effects; however, at present, traditional hydrogels have certain limitations, such as lack of multifunctionality, weak mechanical properties, and sudden increase in drug release, which will affect the efficacy of drugs.

[0005] In this regard, the inventors believe that how to design a composite hydrogel that is multifunctional, has good mechanical properties, and can effectively control the drug release rate and enhance drug stability when combined with drugs is a technical problem that the technicians in this field urgently need to solve; at the same time, the inventors believe that in the treatment of osteoarthritis, how to combine the newly developed composite hydrogel with osteoarthritis treatment to design a drug complex with better drug activity and therapeutic effect is also a technical problem that the technicians in this field urgently need to solve.

[0006] The information disclosed in this background technology section is only intended to enhance the understanding of the overall background of the invention and should not be regarded as an acknowledgment or any form of suggestion that the information constitutes the prior art already known to a person skilled in the art. Summary of the invention

[0007] In view of the above technical problems, the embodiments of the present invention provide a nanocomposite hydrogel based on active oxygen scavenging, and a preparation method and application thereof to solve the problems raised in the above background technology.

[0008] A nanocomposite hydrogel based on active oxygen scavenging comprises: a three-dimensional network skeleton structure formed by cross-linking oxidized chondroitin sulfate and carboxymethyl chitosan, wherein mesoporous polydopamine nanoparticles loaded with melatonin are encapsulated in the three-dimensional network skeleton structure.

[0009] A preparation composition for a nanocomposite hydrogel based on active oxygen scavenging as described above, comprising: oxidized chondroitin sulfate, carboxymethyl chitosan, and mesoporous polydopamine nanoparticles loaded with melatonin; wherein, in the composition, the mass ratio of oxidized chondroitin sulfate, carboxymethyl chitosan, and mesoporous polydopamine nanoparticles loaded with melatonin is 2:5:0.1.

[0010] A method for preparing the above-mentioned nanocomposite hydrogel based on active oxygen scavenging comprises the following steps: S31: Preparation of mesoporous polydopamine nanoparticles; S32: Loading melatonin on mesoporous polydopamine nanoparticles; S33: Mesoporous polydopamine nanoparticles loaded with melatonin are encapsulated in a three-dimensional network skeleton structure formed by cross-linking oxidized chondroitin sulfate and carboxymethyl chitosan to prepare a nanocomposite hydrogel.

[0011] Preferably, step S31 specifically includes: Weigh 0.10 g of poloxamer F127 powder, dissolve it in a solvent with a volume ratio of 1:1 between water and anhydrous ethanol, add 115 μL of TMB solution, and stir with ultrasound until it is completely dissolved to obtain solution 1; Weigh 30.00 mg of dopamine hydrochloride powder and add it to solution 1, then add 200 μL of ammonia water and react at 400 rpm for 24 h to obtain solution 2; The solution 2 after the above reaction was taken, and a mixed solution of anhydrous ethanol and acetone in a volume ratio of 1:1 was centrifuged at 12000 rpm for 20 min and washed 3 times, the product was collected, and the product was freeze-dried to obtain mesoporous polydopamine nanoparticle freeze-dried powder.

[0012] Preferably, step S32 specifically includes: Melatonin was dissolved in methanol to prepare a 10 mg / mL stock solution; The prepared mesoporous polydopamine nanoparticle freeze-dried powder was weighed and dissolved in distilled water to obtain a 1 mg / mL carrier solution. 100 μL of melatonin mother solution was dripped into the carrier solution dropwise and stirred for 24 h. The mixture was centrifuged at 8000 rpm for 10 min, and the supernatant was discarded. The product after discarding the supernatant was freeze-dried to obtain mesoporous polydopamine nanoparticle freeze-dried powder loaded with melatonin.

[0013] Preferably, step S33 specifically includes: Take freeze-dried powder of oxidized chondroitin sulfate and carboxymethyl chitosan powder to prepare solution A and solution B with a mass fraction of 2% respectively; Add 0.01 g of mesoporous polydopamine nanoparticle freeze-dried powder loaded with melatonin to 1 mL of solution C, mix well, then add 1 mL of solution B, and let stand at room temperature for 2 min to obtain a nanocomposite hydrogel.

[0014] Preferably, the method for preparing oxidized chondroitin sulfate freeze-dried powder specifically comprises: Weigh 1.00 g of chondroitin sulfate powder and ultrasonically dissolve it in 10 mL of distilled water to prepare chondroitin sulfate solution; Weigh 0.5 g of sodium periodate powder and dissolve it in 4 mL of distilled water, then add it dropwise into the chondroitin sulfate solution. After reacting for 4 h in the dark, add 1 mL of ethylene glycol and stir for 30 min to terminate the reaction and obtain solution C. Solution C was dialyzed with deionized water and a 3000 DA molecular weight dialysis bag for 3 days, with the water changed 3 times a day, and then freeze-dried at -80°C to obtain oxidized chondroitin sulfate freeze-dried powder.

[0015] A use of the above-mentioned nanocomposite hydrogel based on active oxygen scavenging in the preparation of drugs for treating or improving osteoarthritis.

[0016] Preferably, melatonin in the nanocomposite hydrogel is used to remove reactive oxygen species in cells.

[0017] A nanocomposite hydrogel based on active oxygen scavenging, a preparation method and application thereof provided in an embodiment of the present invention have the following beneficial effects: the present invention combines nanomaterials with the three-dimensional network skeleton structure of hydrogel to develop a new type of nanocomposite hydrogel, and the nanocomposite hydrogel has self-healing ability, good biocompatibility, good mechanical properties, and long-term drug release ability; at the same time, the drug complex prepared by loading melatonin into the nanocomposite hydrogel has better drug activity and therapeutic effect than melatonin, and can more effectively reduce inflammation and oxidative stress and improve symptoms. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Figure 1Schematic diagram of the structure and synthesis of mPDA@Mel@OCS / CMC hydrogel in the present invention; Figure 2 is a Fourier transform infrared spectrum of the oxidized chondroitin sulfate prepared in the present invention; Figure 3 is a hydrogen nuclear magnetic resonance spectrum of oxidized chondroitin sulfate in the present invention; Figure 4 is a scanning electron micrograph of the mPDA@Mel@OCS / CMC hydrogel of the present invention; Figure 5 It is a schematic diagram of the swelling rate results of mPDA@Mel@OCS / CMC nanocomposite hydrogel in the present invention; Figure 6 It is the strain amplitude scanning diagram and step strain diagram of the hydrogel in the present invention at a fixed shear frequency of 5 Hz; in, Figure 6 A is the strain amplitude scanning diagram, Figure 6 B is the step strain diagram; Figure 7 This is a macroscopic image of the self-healing properties of the mPDA@Mel@OCS / CMC hydrogel in the present invention within 20 min; Figure 8 Live and dead staining of cells in the mPDA@Mel@OCS / CMC group; Fig. 9 This is a statistical diagram of the proliferation in the mPDA@Mel@OCS / CMC group of the present invention; Fig.10 This is a schematic diagram of the evaluation results of the anti-inflammatory effect of mPDA@Mel@OCS / CMC on RAW267.4 cells in the present invention. DETAILED DESCRIPTION

[0019] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative work are within the scope of protection of the present invention.

[0020] In view of the above technical problems, the embodiments of the present invention provide a nanocomposite hydrogel based on active oxygen scavenging, and a preparation method and application thereof to solve the problems raised in the above background technology.

[0021] Unless otherwise specified, the materials and reagents used in the following examples can be obtained from commercial sources.

[0022] The design concept of the present invention: 1. The present invention prepares a mPDA@Mel@OCS / CMC nanocomposite hydrogel; the nanocomposite hydrogel is prepared by one step of Schiff base reaction of oxidized chondroitin sulfate (OCS), carboxymethyl chitosan (CMC) and mesoporous polydopamine nanoparticles (mPDA@Mel NPs) loaded with melatonin (Mel); 2. Among them, OCS and CMC are cross-linked to form a three-dimensional network skeleton structure, and mPDA@Mel NPs are uniformly dispersed in the three-dimensional network skeleton structure; the combination of mesoporous polydopamine nanoparticles and the three-dimensional network skeleton structure makes the nanocomposite hydrogel self-healing and biocompatible, and the mPDA@Mel NPs encapsulated in the three-dimensional network skeleton structure can be continuously released, which can become an ideal platform for long-term release of Mel; 3. At the same time, through research, it was found that melatonin has the related effects of directly removing intracellular reactive oxygen species (ROS), improving mitochondrial dysfunction, and inhibiting the generation of ROS and oxidative stress, and melatonin can also directly inhibit the release of pro-inflammatory cytokines, thereby regulating the expression of rhythmic genes regulated by inflammatory mediators, and can block NF-κB signals to delay the progression of OA disease; therefore, in the present invention, the newly developed nanocomposite hydrogel is combined with Mel to develop a drug complex with better drug activity and therapeutic effect; 4. In addition, the nanocomposite hydrogel can realize the concept of "prepared and injected immediately", and the nanocomposite hydrogel allows the on-demand release of mPDA@Mel NPs, providing targeted and timely therapeutic intervention, which meets the requirements of clinical translation. Specific embodiments

[0023] Example 1: Preparation of mPDA@Mel@OCS / CMC nanocomposite hydrogel (1) Preparation of mPDA NPs: Weigh 0.10 g of poloxamer F127 powder, dissolve it in a solvent with a volume ratio of 1:1 between water and anhydrous ethanol, add 115 μL of TMB solution, and stir ultrasonically until it is completely dissolved. Weigh 30.00 mg of dopamine hydrochloride powder, add it to the above dissolved solution, and then add 200 μL of ammonia water. The above reaction system is reacted at 400 rpm for 24 h. Take the above reaction solution, wash it 3 times with a mixed solution of anhydrous ethanol and acetone with a volume ratio of 1:1, centrifuge (12000 rpm, 20 min), collect the product, and freeze-dry it for use.

[0024] (2) Preparation of mPDA@Mel NPs: Mel was dissolved in methanol to prepare a 10 mg / mL mother solution. The prepared mPDA freeze-dried powder was weighed and dissolved in distilled water to obtain a 1 mg / mL carrier solution. 100 μL of the melatonin mother solution was dripped into the carrier solution dropwise and stirred for 24 h. Centrifuged (8000 rpm, 10 min), the supernatant was discarded, and lyophilized for later use.

[0025] (3) Preparation of oxidized chondroitin sulfate (OCS) Weigh 1.00 g of chondroitin sulfate powder and dissolve it in 10 mL of distilled water by ultrasonic. Weigh 0.5 g of sodium periodate powder and dissolve it in 4 mL of distilled water, add it drop by drop into the above chondroitin sulfate solution, protect from light for 4 h, add 1 mL of ethylene glycol and stir for 30 min to terminate the above reaction, dialyze it with deionized water and 3000 DA molecular weight dialysis bag for 3 days, change the water 3 times a day, and then freeze-dry it at -80℃ for later use.

[0026] (4) Preparation of mPDA@Mel@OCS / CMC nanocomposite hydrogel The OCS and carboxymethyl chitosan (CMC) powders prepared in step (3) were prepared into 2% mass fraction solutions C and D, respectively. 0.01 g mPDA@Mel NPs were added to 1 mL of solution C, mixed well, and then 1 mL of solution B was added. The mixture was allowed to stand at room temperature for 2 min to obtain mPDA@Mel@OCS / CMC hydrogel.

[0027] Figure 1 shown; from Figure 1 It can be seen that OCS, CMC and mPDA@Mel NPs interact with each other, and a nanocomposite hydrogel with a three-dimensional network skeleton structure can be synthesized in one step, and mPDA@Mel is uniformly encapsulated in the three-dimensional network skeleton structure.

[0028] Figure 2-3 As shown; compared with the FTIR spectrum of CS, a new peak appears in OCS at 1728cm-1, which is the absorption peak of C=O; at the same time, a new peak exists at 8.2ppm in the 1H NMR spectrum, which proves the successful synthesis of OCS.

[0029] Figure 4 As shown; the results of the scanning electron microscope image show that the nanocomposite hydrogel has a microporous structure with uniform pores and a porosity of about 90%.

[0030] Example 2: Performance Test 1. Study on the swelling properties of mPDA@Mel@OCS / CMC hydrogel in Example 1 (1) Detection method: The mPDA@Mel@OCS / CMC hydrogel in Example 1 was freeze-dried at -80°C (the weight of the hydrogel after freeze-drying was recorded as W0), and then immersed in a PBS buffer at 37°C and pH = 7.4 for 24 hours to ensure that the hydrogel reached a balanced swelling state, and then taken out of the PBS buffer, and after removing excess water (the weight of the hydrogel after removing water was recorded as Ww), the gelation time and swelling rate were tested again. The swelling rate (sr) was calculated according to the following formula: swelling rate (sr) = (Ww-W0) / Ww×100%; (2) Test results: The swelling rate of mPDA@Mel@OCS / CMC prepared in Example 1 is as follows Figure 5 As shown; the results show that the prepared mPDA@Mel@OCS / CMC exhibits good swelling properties, which means that its stability and hydration state in a physiological environment can meet application requirements.

[0031] 2. Exploring the rheological properties of the mPDA@Mel@OCS / CMC hydrogel in Example 1 (1) Rheological test: 1 mL of the mPDA@Mel@OCS / CMC hydrogel in Example 1 was placed on a rheometer (a parallel plate with a size of 20 mm was selected), and then the fixed strain and frequency of the rheometer were set to 1% and 1 Hz, respectively, and a modulus time sweep test was performed; in order to detect the critical strain point in the hydrogel, the strain parameter of the rheometer was set to 0.1% to 1000%, and a modulus strain amplitude sweep test was performed; in order to verify the self-healing ability of the hydrogel, a continuous step strain test was performed at a fixed frequency of 5 Hz (where the oscillating strain alternated between 3% and 300%, with an alternating interval of 120 s); (3) Rheological test results: The storage modulus (G') and loss modulus (G") curves intersect at a strain of about 190%, indicating that the hydrogel network structure is destroyed (e.g. Figure 6 A); on this basis, a continuous step strain test was further carried out. It can be seen that the amplitude oscillation strain changes alternately from 3% to 300%, and the interval of the alternating change is 120s. Under the condition of 300% high strain, G' decreases and is lower than G", and once the strain returns to 1%, G' and G" immediately return to their original values ​​in all cycles (as shown in Figure 6 B), which shows that the hydrogel in Example 1 has the ability to self-heal; in addition, the macroscopic experiment clearly shows that two independent hydrogels can self-heal into a new complete hydrogel within 20 minutes (as shown in FIG. Figure 7 shown).

[0032] 3. Exploring the biocompatibility of mPDA@Mel@OCS / CMC hydrogel in Example 1 (1) Cell culture: 50 μL of mPDA@Mel@OCS / CMC hydrogel was immersed in 1 mL of culture medium for 5 days to obtain mPDA@Mel@OCS / CMC extracts. Then, cells were cultured in the culture medium and mPDA@Mel@OCS / CMC extracts. (2) Determining cell proliferation: The proliferation of the cells in step (1) was determined by the CCK-8 method on days 1, 3, and 7, and the absorbance was measured at 450 nm using a Multiskan microplate photometer (Thermo Fisher Scientific, USA). To further evaluate the proliferation of the cells, the cells cultured for 7 days in step (1) were stained with calcein green and propidium iodide, incubated at 37° C. for 1 h, and then washed three times with PBS buffer solution, and then imaged using a fluorescence microscope. (3) Test results: The results of the cell live-death staining experiment showed that after 3 and 7 days of culture, almost all cells survived, and there was no significant difference between the groups (such as Figure 8 Similarly, the results of the CCK-8 experiment showed that the number of cells in each group increased over time, but the difference between the groups was not significant (as shown in Fig. 9 In summary, the mPDA@Mel@OCS / CMC hydrogel in this application has good biocompatibility.

[0033] 4. Exploring the anti-inflammatory effect of mPDA@Mel@OCS / CMC hydrogel in Example 1 RAW264.7 cells were seeded in six-well plates and induced by LPS for 24 h to polarize them into M1 macrophages. The extract was added to the well plate and cultured for 12 h. The culture medium was aspirated, washed with PBS, and then the DCFH-DA probe was added. The cells were incubated at 37°C for 30 min, aspirated, washed with PBS, and observed under a microscope and photographed.

[0034] Test results: The DCFH-DA experimental results showed that after the addition of LPS, intracellular ROS increased rapidly. After the addition of Mel alone, intracellular ROS was partially eliminated. After the addition of mesoporous polydopamine nanoparticles loaded with melatonin (mPDA@Mel NPs group), intracellular ROS was mostly eliminated. However, after the addition of the composite nano-hydrogel of the present invention, ROS was completely eliminated (mPDA@Mel-AB NPs group), producing a significant anti-inflammatory effect. Therefore, the mPDA@Mel@OCS / CMC hydrogel in this application has good anti-inflammatory activity.

[0035] The embodiments described above are only descriptions of the preferred implementation modes of the present invention, and are not intended to limit the scope of the present invention. Without departing from the design spirit of the present invention, various modifications and improvements made to the technical solutions of the present invention by ordinary technicians in this field should fall within the protection scope determined by the claims of the present invention.

Claims

1. A nanocomposite hydrogel based on active oxygen scavenging, characterized in that: include: A three-dimensional network skeleton structure is formed by cross-linking oxidized chondroitin sulfate and carboxymethyl chitosan, and mesoporous polydopamine nanoparticles loaded with melatonin are encapsulated in the three-dimensional network skeleton structure.

2. A composition for preparing a nanocomposite hydrogel based on active oxygen scavenging as claimed in claim 1, characterized in that: include: Oxidized chondroitin sulfate, carboxymethyl chitosan, and mesoporous polydopamine nanoparticles loaded with melatonin; wherein, in the composition, the mass ratio of oxidized chondroitin sulfate, carboxymethyl chitosan, and mesoporous polydopamine nanoparticles loaded with melatonin is 2:5:0.

1.

3. A method for preparing a nanocomposite hydrogel based on active oxygen scavenging as claimed in claim 1, characterized in that: The following steps are involved: S31: Preparation of mesoporous polydopamine nanoparticles; S32: Loading melatonin on mesoporous polydopamine nanoparticles; S33: Mesoporous polydopamine nanoparticles loaded with melatonin are encapsulated in a three-dimensional network skeleton structure formed by cross-linking oxidized chondroitin sulfate and carboxymethyl chitosan to prepare a nanocomposite hydrogel.

4. The method for preparing a nanocomposite hydrogel based on active oxygen scavenging according to claim 3, characterized in that: Step S31 specifically includes: Weigh 0.10 g of poloxamer F127 powder, dissolve it in a solvent with a volume ratio of 1:1 between water and anhydrous ethanol, add 115 μL of TMB solution, and stir with ultrasound until it is completely dissolved to obtain solution 1; Weigh 30.00 mg of dopamine hydrochloride powder and add it to solution 1, then add 200 μL of ammonia water and react at 400 rpm for 24 h to obtain solution 2; The solution 2 after the above reaction was taken, and a mixed solution of anhydrous ethanol and acetone in a volume ratio of 1:1 was centrifuged at 12000 rpm for 20 min and washed 3 times, the product was collected, and the product was freeze-dried to obtain mesoporous polydopamine nanoparticle freeze-dried powder.

5. The method for preparing a nanocomposite hydrogel based on active oxygen scavenging according to claim 3, characterized in that: Step S32 specifically includes: Melatonin was dissolved in methanol to prepare a 10 mg / mL stock solution; The prepared mesoporous polydopamine nanoparticle freeze-dried powder was weighed and dissolved in distilled water to obtain a 1 mg / mL carrier solution. 100 μL of melatonin mother solution was dripped into the carrier solution dropwise and stirred for 24 h. The mixture was centrifuged at 8000 rpm for 10 min, and the supernatant was discarded. The product after discarding the supernatant was freeze-dried to obtain mesoporous polydopamine nanoparticle freeze-dried powder loaded with melatonin.

6. The method for preparing a nanocomposite hydrogel based on active oxygen scavenging according to claim 3, characterized in that: Step S33 specifically includes: Take freeze-dried powder of oxidized chondroitin sulfate and carboxymethyl chitosan powder to prepare solution A and solution B with a mass fraction of 2% respectively; Add 0.01 g of mesoporous polydopamine nanoparticle freeze-dried powder loaded with melatonin to 1 mL of solution C, mix well, then add 1 mL of solution B, and let stand at room temperature for 2 min to obtain a nanocomposite hydrogel.

7. The method for preparing a nanocomposite hydrogel based on active oxygen scavenging according to claim 6, characterized in that: The preparation method of oxidized chondroitin sulfate freeze-dried powder specifically comprises: Weigh 1.00 g of chondroitin sulfate powder and ultrasonically dissolve it in 10 mL of distilled water to prepare chondroitin sulfate solution; Weigh 0.5 g of sodium periodate powder and dissolve it in 4 mL of distilled water, then add it dropwise into the chondroitin sulfate solution. After reacting for 4 h in the dark, add 1 mL of ethylene glycol and stir for 30 min to terminate the reaction and obtain solution C. Solution C was dialyzed with deionized water and a 3000 DA molecular weight dialysis bag for 3 days, with the water changed 3 times a day, and then freeze-dried at -80°C to obtain freeze-dried powder of oxidized chondroitin sulfate.

8. Use of the active oxygen scavenging nanocomposite hydrogel according to claim 1 in preparing a drug for treating or improving osteoarthritis.

9. Use of the active oxygen scavenging nanocomposite hydrogel according to claim 8 in preparing a drug for treating or improving osteoarthritis, characterized in that: Melatonin in the nanocomposite hydrogel was used to scavenge intracellular reactive oxygen species.

Citation Information

Patent Citations

  • Preparation method of polysaccharide-based hydrogel crosslinked by dynamic imine linkages

    CN107964105A

  • Composite hydrogel capable of promoting chondrogenesis, and preparation method and application thereof

    CN111821513A

  • Injectable drug-loaded hydrogel as well as preparation method and application thereof

    CN118059031A

Cited By

  • Piezoelectric hydrogel loaded with amino-functionalized Mn-ZnO nanoparticles as well as preparation method and application of piezoelectric hydrogel

    CN120617615A

  • Lebupivacaine hydrochloride-bFGF composite gel for postoperative wound analgesia and repair as well as preparation method and application of lebupivacaine hydrochloride-bFGF composite gel

    CN121868457A